Pengembangan Media Wayang Interaktif untuk Pembelajaran Bahasa Jawa Siswa Kelas IV Sekolah Dasar - Ratna Sari; Sripit Widiastuti; Desy Anindia Rosyida (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2025)
This study aims to develop an interactive puppet learning media to enhance the interest and understanding of fourth-grade students in the Javanese language. The method used is Research and Development (R&D), which includes needs analysis, design, development, and media trials. Observational results show that students struggle with understanding Javanese vocabulary and etiquette, which affects their comprehension. The interactive puppet media is expected to serve as a solution to capture students' attention and enrich their learning experience. This media presents content visually and engagingly, facilitating the understanding of difficult concepts, and offering a more interactive learning experience. Validation from content, language, and media experts indicates that this media is suitable for use in Javanese language learning. This study is expected to improve the quality of Javanese language education in elementary schools, particularly in fourth-grade classes, and encourage students to further explore Javanese culture.